THE IMPACT OF OWNERSHIP, DEBT COVENANTS, AND TAX BURDEN ON TRANSFER PRICING: EVIDENCE OF INSTITUTIONAL OWNERSHIP AS A MODERATOR - Rizki Maneges, Gladis; Solikhah, Badingatus (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2026)
Transfer pricing is a crucial issue in profit allocation, corporate governance of multinational firms, and tax management. This study examines how foreign ownership, debt covenants, and corporate tax burden affect transfer pricing, using institutional ownership as a moderating variable. Using moderated regression analysis, the sample comprises 4,083 firm-year observations of non-financial firms registered on the Indonesia Stock Exchange between 2020 and 2024. The results of this study indicate a positive effect of foreign ownership, debt agreements, and corporate tax burden on transfer pricing. Institutional ownership does not moderate the effect between debt covenants and transfer pricing, but weakens the effect between foreign ownership and corporate tax burden on transfer pricing. These findings suggest that transfer pricing practices are related to ownership structure, financial pressures, and tax incentives, with internal governance mechanisms potentially acting as moderators. This study extends agency theory and positive accounting theory by offering practical insights for regulators in strengthening oversight mechanisms for multinational corporations.